Incorporación De Regulaciones Normativas En La Ley De Propiedad Intelectual Para Evitar Actos De Corrupción Suscitados En Las Sociedades De Gestión Colectivas - Burbano Clerque, María Antonieta (2016)
This research exposes the importance of incorporating normative regulations in Intellectual Property Law societies of collective management, because the lack of these has led to countless committing irregularities. So we can see that there is a lack of transparency in the information related to the collection and distribution processes for partners; not kept up to date records of mandates or adhesion contracts, agreements or contracts of reciprocity, appointments, regulations and reforms arising from the same since there is no correlation between information that enters the base of the unit Societies collective management Ecuadorian Institute of Intellectual Property internal each collecting society bases, so you can not get accurate reports. The main objective is to demonstrate that there is a need to incorporate statutory regulations governing the Intellectual Property Law, since when performing a detailed analysis of audit reports poor results have been obtained by the lack of control of these companies.